INCREASING KINDERGARTEN STUDENTS’ VOCABULARY IN NIDA SUKSA SCHOOL, SOUTH THAILAND - Nuraeni .; Haddad Alwi Dalimunte (Program Studi Teknologi Pendidikan FKIP Universitas Ibn Khaldun, Bogor, 2020)
English is international language, which already used in lot of country. Whichmeans when we learn English, it will make us easier to interact with foreigners, adapted in another country. That’s why almost every school insert English in their curriculum. Same as another country, Thailand also, insert English to their curriculum, start from anuban (kindergarten students). As a teacher, teaching kindergarten students vocabulary is very important. In this case the researcher uses flashcards and drilling as methods to increase kindergarten students vocabularies. This research implemented narrative inquiry as method. And the location of this research in Nida Suksa School, Ban Dan, Songkla,Thailad